Charges of monopole operators in ADE ̂ $$ \hat{ADE} $$ Chern-Simons quiver gauge theories - Moumita Patra (Journal of High Energy Physics, 2020)
Abstract We compute R-charges of the BPS-monopole operators in N $$ \mathcal{N} $$ = 3 ADE ̂ $$ \hat{ADE} $$ Chern-Simons quiver gauge theories, along the lines of the work of Benna, Klebanov and Klose in [1]. These theories have a weakly coupled UV completion in terms of N $$ \mathcal{N} $$ = 3 supersymmetric Chern-Simons Yang-Mills theories. In the UV limit the monopole operators are well approximated by classical solutions. We construct classical BPS and anti-BPS monopole solutions to these theories which preserve 1 3 $$ \frac{1}{3} $$ supersymmetry all along the RG flow. We compute the SU(2) R charges in these backgrounds and show that the smallest possible value of quantised SU(2) R charge is zero in each quiver theory.